A clinicoetiological study of vulvovaginitis in a tertiary care hospital - Mahur, Jayalaxmi; Humera, Aisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Vulvovaginitis is a common unavoidable health problem encountered in a woman’s life. Because of its recurrent and persistent symptoms, it leaves a negative impact on the quality of woman’s life and its management poses a challenge. This study is aimed to analyse the clinical profile, clinical symptoms - presentations and various etiological agents in vulvovaginitis. Methods: A study of 125 cases of vulvovaginitis in the age group of 18-50 years was done. This study was based on the data collected like - age, parity, symptoms, clinical presentations and cytological findings. Speculum examination was done with the given consent and high vaginal swabs were taken for cytological study. Based on Amsel’s criteria bacterial vaginosis was confirmed, trichomoniasis by wet mount examination and candidiasis by culture study were confirmed. Results: The present study showed maximum incidence of vaginitis 63.2% among 21-30 years age group, more common in multiparous women 44.8% and vaginal discharge was the commonest symptom 88%. Cytological study showed 53.6% bacterial vaginosis BV), 27.2% vulvovaginal candidiasis (VVC), 2.4% trichomoniasis and remaining 17% mixed infections like BV + VVC 15.2% and 1.6% BV + VVC + Trichomoniasis. Conclusions: All women of reproductive age should have mandatory regular evaluation for early detection and proper management of vulvovaginitis. Creating awareness among women improves their quality of life.